2013
DOI: 10.1007/s10552-013-0299-5
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in red meat and poultry intake and breast cancer risk

Abstract: Purpose Research on the role of red meat and poultry consumption in breast carcinogenesis is inconclusive, but the evidence in African American (AA) women is lacking. The association between consuming meat and breast cancer risk was examined in the Women’s Circle of Health Study involving 803 AA cases, 889 AA controls, 755 Caucasian cases, and 701 Caucasian controls. Methods Dietary information was collected using a Food Frequency Questionnaire. Odds ratios (OR) and 95% confidence intervals (CI) were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 52 publications
3
13
0
1
Order By: Relevance
“…This study showed also clearly how vegetable intakes may differentially decrease the breast cancer risk 2.5 fold for lettuce, 3.63 fold for cabbage,5.4 fold for pea and 7.52 fold carrot in Iranian population. Overall, associations between breast cancer risk and consumption of red meat and poultry were of different magnitude in Asian African and Caucasian women, with further differences noted by menopausal and hormone receptor status in Caucasian women has been reported recently which had examined racial differences in meat and breast cancer risk and represents some of the first evidence in Asian American women (Chandran et al, 2013) which wasn't similar to our results in Iranian population.…”
Section: Discussionsupporting
confidence: 58%
“…This study showed also clearly how vegetable intakes may differentially decrease the breast cancer risk 2.5 fold for lettuce, 3.63 fold for cabbage,5.4 fold for pea and 7.52 fold carrot in Iranian population. Overall, associations between breast cancer risk and consumption of red meat and poultry were of different magnitude in Asian African and Caucasian women, with further differences noted by menopausal and hormone receptor status in Caucasian women has been reported recently which had examined racial differences in meat and breast cancer risk and represents some of the first evidence in Asian American women (Chandran et al, 2013) which wasn't similar to our results in Iranian population.…”
Section: Discussionsupporting
confidence: 58%
“…Adherence to red and processed meat intake recommendations was also inversely associated with breast cancer risk in two previous cohort studies, but positively associated in a prior case‐control study . Red and processed meat are known to have carcinogenic compounds, but associations and potential mechanisms for breast cancer remain unclear …”
Section: Discussionmentioning
confidence: 90%
“…33 Red and processed meat are known to have carcinogenic compounds, 40 but associations and potential mechanisms for breast cancer remain unclear. 41,42 No previous prospective cohort studies have evaluated whether the benefits of adherence differed between premenopausal and postmenopausal cancer, but current evidence indicates there may be differences in the etiology of premenopausal and postmenopausal breast cancer. 4 Associations in two prior case-control studies overall did not differ by menopausal status.…”
Section: Discussionmentioning
confidence: 99%
“…A pooled analysis of 8 additional cohort studies reported no association with processed meats [18]. In addition, among 7 population-based case-control studies that considered processed meats separately from unprocessed red meat, 5 reported a positive association with processed meats [36, 54–57], and 2 reported non-statistically significant positive associations [39, 58]. Recently, a meta-analysis of all available prospective studies reported a positive association with processed meats and breast cancer risk [59]; however, we note that this study included overlapping studies, therefore the conclusions may not be fully representative of the available data.…”
Section: Discussionmentioning
confidence: 99%
“…Although the poultry association did not retain statistical significance when combining results via meta-analysis for all women combined, there was still evidence of a significant association in stratified analyses by menopausal status. Evidence for poultry and white meat intake is inconclusive, with many investigations of poultry yielding null results [20, 37, 61, 67], with a few finding positive associations with BC risk [40, 58]. Like processed meats, there could be differences in the timing of exposure (e.g.…”
Section: Discussionmentioning
confidence: 99%